Association between Serum Ferritin and Pre-eclampsia (Bangladesh Medical Journal, 2019)
Pre-eclampsia (PE) is a major cause of maternal and prenatal morbidity and mortality in developing countries. PE occurs in about 6% of the general women population. It complicates about 5-15% of pregnancies over 20 weeks and is responsible for 16% of maternal mortality. Pre-delivery serum Ferritin concentration was significantly higher in patients with eclampsia than in healthy pregnant women. The serum ferritin was the best sensitive marker of the iron status parameters reflecting the preeclampsia. The aim of the study is to explore the association between serum ferritin and Preeclampsia and to do a comparison of serum ferritin to assess risk of development preeclampsia between case and control.This is a case-control study with laboratory methods. The study was carried out in Sir Salimullah Medical College and Hospital. Serum Ferritin was tested in the department of biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU). The study was carried out from January 2008 to December 2009 and the sample size was 80. A total of 80 pregnant women, comprising of 40 PE and 40 normotensive primi or multigravida in the third trimester were enrolled in the study. The mean Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP) were significantly higher in PE group on both occasions compared to normotensive women with similar chronological age gestational age. Out of the 40 cases 65% patients had severe proteinuria (+++) and 17.5% had moderate proteinuria (++) and 17.5% had mild proteinuria. The difference between case and control with respect to proteinuria was highly significant. More than two third (67.5%) of the cases did not have any iron deficiency anemia, while the rest (32.5%) had mild iron deficiency anemia. In the present study, the mean serum Ferritin level of PE group was almost 10 times higher (167.11 ± 10.43 ngm/ml) than that of controls (17.0 ± 3.03 ngm/ml) than that of control (431.0 ± 10.93 gm/dl). More than one-third of the cases showed serum ferritin >210 ngm/ml, compared to none of the control group. Serum Ferritin level is significantly higher in preeclamptic patients than the control group.Bangladesh Med J. 2018 Jan; 47 (3): 18-24